Pengaruh Penggunaan Aplikasi Quizizz Paper Mode untuk Motivasi Belajar Siswa Kelas V SDN 21 Pekanbaru: Penelitian - Nur Mellany Paizal; Febrina Dafit (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to increase the capacity of UMKM Kripik Susus "UMMU" Karanganyar actors in utilizing social media as a means of digital marketing. The background of this activity is based on the fact that business actors still rely on conventional marketing strategies and have not optimally utilized digital platforms. Through a participatory approach, this activity involves observation, interviews, training, and technical assistance in eight main aspects: digital marketing strategy, content optimization, collaboration, data analysis, customer engagement, e-commerce integration, increasing consumer trust, and employee training. The results of the activity show an increase in partners' understanding and skills in managing social media accounts, creating interesting content, and building better relationships with customers. Partners have also begun to utilize e-commerce platforms to expand their market reach actively. This program proves that hands-on practice-based assistance can have a real impact on the development of micro-businesses, as well as strengthening the role of universities in empowering the local community economy in the digital era.